Significance of Cellular Senescence in Aging and Cancer - Grimes, Angela (Korean Cancer Association, 2009)
Cellular senescence is a mechanism that induces an irreversible growth arrest in all somatic cells. Senescent cells are metabolically active but lack the capacity to replicate. Evolutionary theories suggest that cellular senescence is related to the organismal decline occurring in aging organisms. Also, such theories describe senescence as an antagonistically pleiotropic process that can have beneficial or detrimental effect on the organism. Cellular senescence is believed to be involved in the cellular changes observed as aging progresses. Accumulation of senescent cells appears to occur widely as the organism ages. Furthermore, senescence is a key element of the tumor suppressor pathways. Therefore, it is part of the natural barrier against the uncontrolled proliferation observed in cellular development of malignancies in multicellular organisms. Activation of the senescence process guarantees a limited number of cellular replications. The genetic network led by p53 is responsible for activation of senescence in response to DNA damage and genomic instability that could lead to cancer. A better comprehension of the genetic networks that control the cell cycle and induce senescence is important to analyze the association of senescence to longevity and diseases related to aging. For these reasons, experimental research both in vitro and in vivo aims to develop anticancer therapies based on senescence activation. The last decade of research on role and function of senescence in aging and cancer are discussed in this paper.